2019
DOI: 10.3390/polym11081260
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Crack Propagation Path of the Veil Interleaved Composite by Fusion-Bonded Dots

Abstract: This study investigated the effect of the fusion-bonded dots of veil interleaves on the crack propagation path of the interlaminar fracture of continuous carbon fiber reinforced epoxy resin. Two thin fiber layers (i.e., nylon veil (NV) with fusion-bonded dots and Kevlar veil (KV) physically stacked by fibers) were used to toughen composites as interleaves. Result shows that the existence of fusion-bonded dots strongly influenced the crack propagation and changed the interlaminar fracture mechanism. The Mode I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The most relevant aspects observed in the analysis of the fracture surfaces of the specimens tested to fatigue under mixed mode I/II loading using the MMB and ADCB test methods are presented below, with the aim of identifying the dominant fracture processes. A JEOL 6610LV scanning electron microscope (SEM) was used for this purpose [35,36]. Starting with the specimens tested by means of the MMB method, Figure 9 shows the region close to the insert used to initiate delamination in a fatigue specimen for a mode mixity ratio of 0.2.…”
Section: Analysis Of Fracture Surfacesmentioning
confidence: 99%
“…The most relevant aspects observed in the analysis of the fracture surfaces of the specimens tested to fatigue under mixed mode I/II loading using the MMB and ADCB test methods are presented below, with the aim of identifying the dominant fracture processes. A JEOL 6610LV scanning electron microscope (SEM) was used for this purpose [35,36]. Starting with the specimens tested by means of the MMB method, Figure 9 shows the region close to the insert used to initiate delamination in a fatigue specimen for a mode mixity ratio of 0.2.…”
Section: Analysis Of Fracture Surfacesmentioning
confidence: 99%
“…Many researches focused on the further enhancement of the mechanical properties of PPTA fibers, including the tensile strength and modulus [5][6][7][8]. Introducing the nanofiller on the surface or internal of the fibers is the one of most commonly strategies, which is expected to reinforce the aramid fiber by combining the two strong materials.…”
Section: Introductionmentioning
confidence: 99%
“…Beckermann et al [ 11 ], Meireman et al [ 12 ], Garcia-Rodriguez et al [ 13 ], Quan et al [ 14 ], Kuwata et al [ 26 , 27 ], Del Saz-Orozco et al [ 31 ], Saghafi et al [ 35 , 36 ], Nash et al [ 37 , 38 ], Guo et al [ 39 ], Chen et al [ 40 ], Ognibene et al [ 41 ], Pozegic et al [ 42 ], Beylergil et al [ 43 , 44 , 45 ], Alessi et al [ 46 ], Barjasteh et al [ 47 ], Monteserin et al [ 48 , 49 ], Daelemans et al [ 50 , 51 , 52 ], De Schoenmaker et al [ 53 ], O’Donovan et al [ 54 ], and Hamer et al [ 55 ] reported that PA veils as interleaves for FRP composite laminates are applicable in either carbon or glass fiber reinforcement. PAs of different classes were used in these studies, such as PA 6 (sometimes, the brand name Nylon is used), PA 11, PA 12, PA 66, and PA 69.…”
Section: Comparative Analysis Of the Toughening Effectmentioning
confidence: 99%